2021
DOI: 10.1101/2021.05.06.442974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endothelial Unc5B controls blood-brain barrier integrity

Abstract: Blood-brain barrier (BBB) integrity is critical for proper function of the central nervous system (CNS). Here, we showed that the endothelial Netrin1 receptor Unc5B controls BBB integrity by maintaining Wnt/β-catenin signaling. Inducible endothelial-specific deletion of Unc5B in adult mice led to region and size-selective BBB opening. Loss of Unc5B decreased BBB Wnt/β-catenin signaling, and β-catenin overexpression rescued Unc5B mutant BBB defects. Mechanistically, Netrin1 enhanced Unc5B interaction with the W… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Canonical Wnt signaling-associated genes Tle3, Tcf7l1, Tcf7, Axin1, and Axin2 were upregulated and Wnt signaling has well established roles in kidney development . Recently, it was shown that netrin-1 enhances the interaction of Unc5b with LRP6, a Wnt co-receptor, thereby activating Wnt/-catenin signaling and linking the two signaling pathways in blood-brain barrier integrity (Boyé et al, 2022). However, with Wnt pathway genes upregulated in the absence of netrin-1, this cooperative signaling may not be active in kidney endothelium.…”
Section: Development • Accepted Manuscriptmentioning
confidence: 99%
“…Canonical Wnt signaling-associated genes Tle3, Tcf7l1, Tcf7, Axin1, and Axin2 were upregulated and Wnt signaling has well established roles in kidney development . Recently, it was shown that netrin-1 enhances the interaction of Unc5b with LRP6, a Wnt co-receptor, thereby activating Wnt/-catenin signaling and linking the two signaling pathways in blood-brain barrier integrity (Boyé et al, 2022). However, with Wnt pathway genes upregulated in the absence of netrin-1, this cooperative signaling may not be active in kidney endothelium.…”
Section: Development • Accepted Manuscriptmentioning
confidence: 99%
“…Different strategies have been employed to improve the BBB penetration proficiency of NPs. Among various approaches, 145−148 a common way is to regulate the Wnt/βcatenin signaling produced by glial cells and reduce their binding to multiprotein receptor complexes on brain ECs 23 for cargo administration with high BBB penetration potential. The main limitation of all these methods, however, could be the structural damage and, hence, the dysfunction of the BBB.…”
Section: Properties Affecting Nanoparticle Crossing Through the Bbbmentioning
confidence: 99%
“…22 Furthermore, the endothelial Wnt/β-catenin pathway has been found to be one of the major molecular drivers of barriergenesis in the brain. 23,24 Hussain et al 25 demonstrated the importance of β-catenin in maintaining BBB integrity using endothelial-specific β-catenin conditional knockout mice. These mice exhibited severe leakage of plasma proteins IgG and albumin into the cerebral cortex.…”
Section: Astrocytesmentioning
confidence: 99%
“…19,20 The entry of suprangiolar vascular endothelial cells into the CNS is accompanied by activation of the Wnt/β-catenin pathway at specific times during the embryonic period. 21 Angiogenesis is a natural defense mechanism that helps restore oxygen and nutrient supply to the affected brain tissue after an IS. Wnt7a/7b participates in angiogenesis in the CNS by activating the Wnt/β-catenin pathway.…”
Section: Introductionmentioning
confidence: 99%